CLINICAL AND HEMATO-BIOCHEMICAL STUDIES ON GOATS NATURALLY INFESTED WITH SUCKING AND BITING LICE - N. Nizamov; P. Iliev (Trakia Journal of Sciences)
The current study was performed to assess the most common clinical symptoms and hemato-biochemical alterations in goats naturally infested with sucking and biting lice. A total of 4599 goats were included in the clinical investigation. The changes in concentrations of some hematological and biochemical parameters were evaluated using 20 naturally infested animals divided into 2 equal groups – group 1 (infested with Bovicola caprae) and group 2 (infested with Linognathus stenopsis). Blood samples were collected before the treatment with Eprinomectin and on the 30th and 60th-day post-treatment (DPT). After sampling, the blood was examined for changes in the complete blood cell count including RBC, HGB, HCT, RBC indices (MCV, MCH, MCHC, RDW), WBC, leukocyte differential count as well as some biochemical parameters (Ca, P, Fe, total protein, albumin, bilirubin, ASAT, ALAT, AP). Clinical demonstrations in infested goats were not specific, represented with rubbing, scratching, broken hairs, alopecia, skin secretion, inflamed lesions (papules), crusts, and keratinization. The changes found in the hematological and biochemical parameters were normocytic hypochromic anemia (p˂0.001) and hypoferremia (p˂0.01) in the goats infested with sucking lice (L. stenopsis) and leukocytosis (p˂0.001), hyperproteinemia (p˂0.001) and hyperalbumineamia (p˂0.05) in the animals infested with biting lice (B. caprae). All changed parameters have returned to the reference ranges on the 30th and 60th DPT.